Automated Technology for Verification and Analysis 7th International Symposium, ATVA 2009, Macao, China, October 14-16, 2009, Proceedings - Liu, Zhiming; Ravn, Anders P. (Programming and Software Engineering, 2009)
This book constitutes the proceedings of the 7th International Symposium on Automated Technology for Verification and Analysis, ATVA 2009, held in Macao, China, in October 2009. The 23 regular papers and 3 took papers presented together with 3 invited talks, were carefully reviewed and selected from 74 research papers and 10 tool papers submissions. The papers are organized in topical sections on state space reduction, tools, probabilistic systems, medley, temporal logic, abstraction and refinement, and fault tolerant systems.